Concordance of caregivers and nutritionist MUAC measurements for acute malnutrition screening among children in rural Zimbabwe: A comparative study of the FL-MUAC Approach - Majiwa, Promise; Chopera, Prosper; Matsungo, Tonderayi Mathew (The North African Journal of Food and Nutrition Research, 2025)
Background: Acute malnutrition in children represents a substantial public health concern, significantly elevating the risk of morbidity and impaired development. The Family-led Mid-Upper Arm Circumference (FL-MUAC) facilitates community-driven early diagnosis and treatment of acute malnutrition, thereby reducing morbidity, mortality, and program expenditures. Aims: This investigation aimed to assess the ability of caregivers to accurately take MUAC measurements in children aged 6–59 months residing in rural Zimbabwean communities. Furthermore, this study aimed to elucidate the factors influencing the caregivers’ ability to measure, focusing on their Knowledge, Attitudes, and Practices (KAPs) related to the FL-MUAC approach. Subjects and Methods: A cross-sectional study utilizing a mixed-methods approach was conducted to collect both quantitative and qualitative data from Seke and Makoni rural districts in Zimbabwe. Multistage stratified random sampling was applied to select caregivers who participated in the study. Quantitative data were analyzed using SPSS version 20, incorporating Pearson’s Chi-square test of association, Bland-Altman plot analysis, and binary logistic regression. Qualitative data were subjected to content analysis. Ethical clearance was obtained from the Medical Research Council of Zimbabwe (MRCZ/B/2223). Results: A total of 96 caregivers were enrolled, yielding a response rate of 87.3%. Bland-Altman plot analysis demonstrated a mean difference close to zero (-0.024 ± 0.479 cm), indicating no statistically significant disparity between maternal and nutritionist-derived measurements. The capacity of caregivers to accurately measure MUAC was significantly associated with geographical proximity to health facilities (p = 0.001). Furthermore, maternal nutrition knowledge scores were identified as a significant determinant of MUAC measurement accuracy (p = 0.044) In 93.8% of cases, mothers demonstrated accurate MUAC measurement following adequate training. Conclusions: This study establishes that, with appropriate exposure, maternal MUAC measurements exhibit a high degree of concordance with those obtained by nutritionists. Maternal nutrition knowledge scores significantly influence MUAC measurement accuracy. Therefore, the FL-MUAC approach demonstrates significant potential for enhancing community-based early diagnosis and management of acute malnutrition in this and comparable resource-constrained settings. Keywords: Mid-Upper Arm Circumference, Severe acute malnutrition, Family-led MUAC, malnutrition screening, Zimbabwe.